Tribological performance of novel modified calophyllum inophyllum nano-fluid from Pahang, Malaysia - Amiril Sahab, Abdul Sani; Zubaidah, Zamri; Radhiyah, Abd Aziz; Ainaa Mardhiah, Sabri; Norfazillah, Talib (Malaysian Tribology Society (MYTRIBOS), 2024)
This study aims to examine the performance of modified Calophyllum Inophyllum oil (MCIO) added with activated carbon made from the Calophyllum Inophyllum (CI) fruit shells as nano additives to enhance the oil performance as lubricants on friction and wear characteristics. This ecofriendly nanofluid is formulated by combining the nanoactivated carbon with MCIO using homogenization and sonication techniques. These nanofluid samples are subjected to physical analysis according to ASTM standards to determine their kinematic viscosity and viscosity index. A four-ball wear test is conducted for investigating the fluid's tribological performance. It was revealed that the formulation of MCIO containing 0.025 wt. % nano-activated carbon has the lowest coefficient of friction of 0.0551, with wear scar diameter of 724.2 µm and wear rate 5.91 × 10-7 mm. The novel MCIO with activated-carbon nano additive demonstrated superior lubricant performance compared to synthetic ester, neat MCIO, and MCIO + 0.025 wt. % NC based on the tribological performance shown.